Evaluation of effects of anti-vibration gloves on manual dexterity. Issue 11 (2nd November 2018) - Yao, Yumeng; Rakheja, Subhash; Gauvin, Chantal; Marcotte, Pierre; Hamouda, Karim
Abstract: The purpose of this study was to evaluate the effects of anti-vibration gloves on manual dexterity and to explore factors affecting the manual dexterity. The manual dexterity of ten different gloves was investigated with 15 adult male subjects via performing two different dexterity tests, namely ASTM F2010 standard test and Two-Hand Turning and Placing Minnesota test. Two-factor repeated-measures analysis of variance was conducted to evaluate the main effects of glove type, test method and their interaction effect on manual dexterity. Results suggested that glove type yielded significant effect on manual dexterity ( p  < .001), while no significant difference was observed between test methods ( p  = .112). The interaction effect of glove type and test method also revealed a significant difference ( p  = .009). The manual dexterity decreased nearly linearly with increase in the glove thickness, which further showed a moderately significant difference on the number of drops during the tests. Practitioner Summary: Anti-vibration gloves may adversely affect manual dexterity and work precision, which may discourage their usage. This article presented a study of manual dexterity performance of anti-vibration gloves and the design factors affecting the manual dexterity. The results were discussed in view of a design guidance for improved hand dexterity, which would encourage the use of anti-vibration gloves in the workplace.